The independence of judges - Engstad, Nils Asbjørn; Frøsetg, Astrid Lærdal; Tønder, Bård (Eleven International Publishing, 2014)
An independent judiciary is crucial for upholding the rule of law and for the protection of human rights in a democratic society. The Independence of Judges is an anthology, illustrating that there is still a need for further exploration and reflection on various aspects of the principle of judicial independence. The book presents 22 articles, written from different perspectives and analyses by judges, lawyers, public prosecutors, and scientists in the areas of law, social sciences, and media science. The book's contributions provide an overview of historical developments, as well as issues of.